Performance Evaluation of a Drinking Water Treatment Plant in Samaipata, Bolivia - Braun, Michaela (My University, 2019)
Unsafe water and a lack of basic sanitation causes nearly 80 percent of all sicknesses and diseases in the world. The provision of safe drinking water on community water level, especially in Bolivia one of the poorest countries of South America, faces major challenges in regard of a lack of investment in the water and sanitation sector, in the conditions of the water infrastructure, and of public appreciation for the value of water. A drinking water treatment plant for a population of 4,935 inhabitants in Samaipata in Bolivia was evaluated in terms of performance, design, operation, and maintenance. The thesis aimed to identify technical problems and deficiencies in operation of the plant, and to introduce suitable treatment measures for the source El Fuerte and the well La Carretera to the responsible Water Cooperative of the village. The risk of contamination for both sources was assessed by a protocol for sanitary facilities. Water samples were taken to identify whether suitable treatment technologies for the types of water source are provided. The performance of each treatment step in the plant was studied by inspection and water analyses at different points in the treatment chain. Jar tests were performed with Al2(SO4)3, Al2(SO4)3 and lime, FeCl3 and FeSO4. The plant was operated for 4.5 h with an increased dosage of 15 mg/l of Aluminum Sulfate. A Microbial Barrier Analysis (MBA) and Quantitative Microbial Risk Assessment (QMRA) were performed to assess the health risk based on the Water Safety Plan concept. Less source protection, lack of skilled expertise in operation, deficiency of guidance from the administration, insufficient design and equipment, and incomplete technologies are identified as the main issues in this study. Recommendations in a two-step implementation plan are presented to provide of an adequate water supply in Samaipata.
Keywords: Bolivia; Water Treatment Plant; Water Quality; Water Cooperative; Turbidity; Samaipata; QMRA; Performance Evaluation; Operation; MBA; Maintenance; Jar Test; Health Risk Assessment; Drinking Water; Developing Countries